1999
DOI: 10.1002/(sici)1098-2361(1999)18:2<101::aid-zoo2>3.3.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal behavior in a group of unchained female African elephants

Abstract: The chaining of elephants at night is a common management strategy in zoos, yet the costs and benefits of such a strategy are relatively unknown. A study of three unchained female African elephants was undertaken to document their nocturnal behavior. The subjects were observed between the hours of 1800 and 0800 for 10 weeks in the summer of 1992 (total of 172 hr) and 14 weeks in the summer of 1994 (total of 153 hr). Scan data were collected every 5 min to gather information on activity budgets, social proximit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 0 publications
4
33
1
Order By: Relevance
“…In one study of a single captive female African elephant, less time was spent feeding at night (about 13% of the night when outside and about 32% of the night inside) than during the day (about 38% outside and 43% inside). Three female African elephants at Zoo Atlanta were found to feed for about 47% of the time, between 17:00 and 08:00 hr (Wilson et al, 2006), which is similar to previous studies by Brockett, Stoinski, Black, Markowitz, and Maple (1999) on the same group of elephants (41.91% nocturnal feeding time in 1992 and 34.84% in 1994).…”
Section: Eating Behaviorsupporting
confidence: 87%
See 1 more Smart Citation
“…In one study of a single captive female African elephant, less time was spent feeding at night (about 13% of the night when outside and about 32% of the night inside) than during the day (about 38% outside and 43% inside). Three female African elephants at Zoo Atlanta were found to feed for about 47% of the time, between 17:00 and 08:00 hr (Wilson et al, 2006), which is similar to previous studies by Brockett, Stoinski, Black, Markowitz, and Maple (1999) on the same group of elephants (41.91% nocturnal feeding time in 1992 and 34.84% in 1994).…”
Section: Eating Behaviorsupporting
confidence: 87%
“…The elephants in the current study are not chained. Brockett et al (1999) also found less variation in lying down time than in the current study. The African elephants in their study spent about 32% of the night (4.8 hrs) lying down in 1992 and about 33% of the night (4.6 hrs) lying down in 1994.…”
Section: Lying Down Behaviorcontrasting
confidence: 55%
“…At the time of the study, the animals were estimated to be 17, 16, and 16 years of age. All observations were conducted during the day while the animals were in their outdoor exhibit [see Brockett et al, 1999 for a description of the housing conditions]. The normal husbandry routine for the subjects was as follows: the subjects were released into the outdoor exhibit at approximately 9:00 AM without their human handlers with approximately 23 kg of Bermuda hay to be consumed by all three individuals.…”
Section: Methods Subjectsmentioning
confidence: 99%
“…Group formation is a widespread phenomenon throughout the animal kingdom, occurring in a wide range of taxa (Parrish & Edelstein-Keshet 1999) both in wild and domestic animals ( Webster & Hurnik 1994;Brockett et al 1999;Ruckstuhl 1999). Evolutionary theories suggest that joining a group increases the organisms' fitness (Parrish & Edelstein-Keshet 1999) by reducing the chance of being caught by a predator, increasing the foraging efficiency and reducing energy costs ( Ruckstuhl & Neuhaus 2001;Krause & Ruxton 2002).…”
Section: Introductionmentioning
confidence: 99%